Biogenic silver nanoparticles as antifungal agents - Mussin, Javier; Giusiano, Gustavo (Frontiers in Chemistry, 2022)
In recent years, an increase in multidrug-resistant fungal strains has been observed, which, together with the limited number of clinically available antifungal agents, highlights the need for the development of new antifungal agents. Due to the proven antifungal activity of silver nanoparticles (AgNPs), there is a growing interest in their use in the treatment of fungal infections. Nanoparticles are usually synthesised through a variety of physical and chemical processes that are costly and pollute the environment. For this reason, biogenic synthesis is emerging as an environmentally friendly technology and new strategies are increasingly based on the use of biogenic AgNPs as antifungal agents for clinical use. The aim of this review is to compare the antifungal activity of different biogenic AgNPs and to summarise the current knowledge on the mechanisms of action and resistance of fungi to AgNPs. Finally, a general analysis of the toxicity of biogenic AgNPs in human and veterinary medicine is performed.